The 2020 United Nations human rights treaty body review process: prioritising resources, independence and the domestic state reporting process over rationalising and streamlining treaty bodies. Issue 8 (14th September 2021) - Sarkin, Jeremy
ABSTRACT: This article reflects concerns about what may emerge from the United Nations human rights treaty body (TB) review process that began in April 2020. The fear specifically is what the outcome of that review may be and whether the goal of strengthening and/or streamlining TBs will actually result in a less robust state oversight and human rights compliance methodology in the future. Already TBs have been weakened by being granted fewer resources, which causes strains on the system, and by steps to make the procedures easier, less cumbersome, less duplicative, less time-consuming, and less resource-intensive for states. This article maintains, however, that more emphasis ought in fact to be placed on enhancing the resources available to these institutions, and on strengthening their roles in a variety of ways, including by increasing their independence as a means to improve their performance. It claims that if streamlining TBs means reducing what impact these bodies can have, this ought to be avoided. The article also stresses that if the domestic component of the state reporting process is enhanced, and the national follow-up procedures and processes further developed, the TB process will see improvements, both in its functioning and in its role in promoting and protecting human rights in states. It is thus reasoned that the global push to create and promote national reporting mechanisms ought to be supported.